Efektivitas Penggunaan Media Sosial sebagai Sarana Pembelajaran Interaktif di Kalangan Mahasiswa - Moh Mundzir (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Social media has become an integral part of students’ lives and is increasingly being used as a means of interactive learning. This study aims to analyze the effectiveness of social media use in supporting students’ learning process, by highlighting the benefits, challenges, and solutions that can be applied. The research method used is a qualitative approach with case studies, in-depth interviews, and thematic analysis. The results of the study indicate that social media provides flexibility in accessing learning materials, increases academic engagement, and facilitates discussion and collaboration between students and lecturers. However, there are several challenges, such as distraction, unguaranteed validity of information, lack of structure in learning, and gaps in access to technology. To overcome these challenges, strategies are needed such as good time management, increasing digital literacy, active roles of lecturers in directing learning, and institutional support in increasing access to technology. With the implementation of the right strategy, social media can be an effective tool in supporting interactive learning, improving students’ academic quality, and encouraging educational transformation in the digital era.